Subcooled flow boiling heat transfer in a microchannel with chemically patterned surfaces. (September 2019) - Wang, Hongzhao; Yang, Yinchuang; He, Minghao; Qiu, Huihe
Highlights: Wettability patterned surface can achieve higher HTC than homogeneous hydrophilic surfaces for subcooled flow boiling in a microchannel. Patterns can control the nucleation sites and confine the bubble shapes in flow boiling. Wettability patterned surface can improve the bubble mobility in comparison with homogeneous surface. Mass flux affects the subcooled flow boiling heat transfer performance in a patterned microchannel. Abstract: In this paper, we explore subcooled flow boiling in a microchannel with a chemically patterned surface. The effects of wettability patterns on bubble dynamics and heat transfer are reported and compared with those in a homogenous hydrophilic microchannel. The microchannel has a hydraulic diameter of 311.76 µm and a length of 20 mm. The mass flux of water ranges from 103 kg/m 2 s to 203 kg/m 2 s and the heat flux ranges from 2.56 W/cm 2 to 78.61 W/cm 2 . It is found that the heat transfer coefficient ( HTC ) in the wettability-patterned microchannel is about 22% higher than that in the homogenous hydrophilic microchannel. The mechanism behind the heat transfer enhancement is that the nucleation easily occurs on the hydrophobic dots and the bubbles on the patterned surface show higher mobility and longer triple contact line. In addition, the mass flux effect on flow boiling in the wettability-patterned microchannel is investigated and it is found that the HTC improves as the mass flux increases. To understand the local forces required for bubble departure in a wettability-patterned microchannel, an analytical model is developed. The analytical results show that the local bubble detaching force will decrease on a chemically patterned surface compared to a homogenous hydrophobic surface, which also gives a useful insight to combine different wettability characteristics to increase bubble mobility and then improve flow boiling heat transfer in a microchannel.